Experimental research on remaining oil distribution and recovery performance after immiscible and miscible CO2-WAG injection by direct visualisation. (2017) - Han, Hongyan; Li, Tianxin; Song, Hongqing; Wang, Yuhe; Killough, John
More than half of oil remains in the reservoir pores after water flooding. A microscopic visualised physical model under high temperature and pressure was created to simulate a reservoir pore network. It is an efficient way to study the formation and distribution of microscopic remaining oil which can enhance oil recovery. Displacement mechanisms were researched for CO2 /water alternative flooding (CO2 -WAG). The remaining oil morphology and migration characteristics were directly observed and analysed. The distribution of the remaining oil of models in different flooding stages was quantitatively obtained by grey images processing technology. Comparing the distribution of different occurrences of microscopic remaining oil, the multiphase fluid transport characteristics in the experimental porous media is described. Experimental results show that the recovery efficiency under the CO2 -oil miscible state can be enhanced 5.75% more than the immiscible state. There exist four types of remaining oil after CO2 -WAG with different effects, namely: 1) clusters; 2) columnar; 3) membrane; 4) blind-end remaining oil. Miscible CO2 -WAG could efficiently improve oil recovery of cluster, column, and membrane types of remaining oil. Immiscible CO2 -WAG only caused an obvious recovery improvement for the cluster type of remaining oil. In order for CO2 -WAG flooding to be used to improve oil recovery most efficiently, the occurrence state and distributions of remaining oil should first be considered. [Received: June 23, 2015; Accepted: March 1, 2016]